Translation Strategies and Quality of Metaphor in “Twilight” Novel By Stephanie Meyer - Ningtyas, Hajar Mutiara; Faridi, Abdurrahman; Sutopo, Djoko (Universitas Negeri Semarang, 2021)
This study focused on the analysis of the translation strategies and resulted translation quality in rendering metaphors found in the Twilight novel. The analysis involved the translation strategies by Newmark (1988) and translation quality by Hartono (2016). The results showed that there were seven translation strategies utilized by the translator in rendering the metaphors in the Twilight novel from Indonesian into English with total metaphors were 164. Those metaphors were translated using translation strategies: reproducing the same metaphorical image in the target language 48 times (29%), replacing the metaphorical image in the source language with a standard metaphorical image in the target language with 25 times (15%), translating metaphor by simile by maintaining the metaphorical image with 20 times (12%), translating metaphor by simile plus sense with 13 times (8%), converting a metaphor to its sense or meaning only with 44 times (29%), deleting metaphor with 7 times (4%), and translating metaphor by the same metaphor with the sense or meaning added with 7 times (4%). In terms of content quality, the translation of metaphors was dominated by good content, presentation, and mechanics quality. Moreover, the application of each translation strategy would result in different types of translation quality in terms of content, presentation and mechanics. In addition, it is suggested that the employment of translation strategy in rendering metaphor should consider deeply the existence of the same metaphor both in the source language and target language because the quality of the translation will be determined by the translation strategies.